Revisiting the entrepreneurial mind : inside the black box - Brännback, Malin, 1963-; Carsrud, Alan L. (Springer, 2017)
The book explores various aspects of cognitive and motivational psychology as they impact entrepreneurial behavior. Building upon the 2009 volume, Understanding the Entrepreneurial Mind, the editors and contributors explore the cognitions, motivations, passions, intentions, perceptions, and emotions associated with entrepreneurial behaviors, in each case preserving their original chapters and enhancing them with thoughtful and targeted updates, reflecting on the most recent developments in theory and practice, telling the story of what has transpired in the last decade in the field of entrepreneurial psychology. The volume addresses such questions as: Why do some people start business and others do not? Is entrepreneurship a natural quality or can it be taught? Do entrepreneurs think differently from others? While there is a great deal of literature exploring the dynamics of new firm creation, policies to promote innovation and technology transfer, and the psychology of creativity; research on entrepreneurial mindset or cognition is relatively new, and draws largely from such related fields as organizational behavior, cognitive and social psychology, career development, and consumer research. In this book, editors Brännback and Carsrud have reassembled the contributors to Understanding the Entrepreneurial Mind to discuss new research paradigms given their vantage point years after the original volume was published. Featuring the most current literature references, Revisiting the Entrepreneurial Mind continues to challenge conventional approaches to entrepreneurship and articulate an agenda for future research.
Keywords: Entrepreneurship -- Psychological aspects.; Businesspeople -- Psychology.; elektronické knihy; electronic books